2015
DOI: 10.1093/cje/bev065
|View full text |Cite
|
Sign up to set email alerts
|

Rates of return on capital across the world: are they converging?

Abstract: This article estimates levels and identifies trends in the profitability of capital in a broad sample of developed, developing and post-communist transition economies making up over 80% of global output. The underlying distributional and efficiency determinants of profitability are considered in the Marxian analytical framework. For the period of 1995-2007 leading to the Great Recession, our estimates indicate a trend towards convergence of national profit rates largely driven by the convergence of profitabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 48 publications
0
10
1
Order By: Relevance
“…Our estimation of macroeconomic ROR is comparable to these in the literature. The majority of the crosscountry studies report highest average ROR to be found in less developed economies (Bigsten, 2000;Banerjee and Duflo, 2005;Izyumov and Alterman, 2005;Bai et al, 2006;Lu and Gao, 2009;Udry and Anagol, 2006;Chou et al, 2016). However our results differ from those reported in Caselli and Feyrer (2007) and some of the follow-up papers including Mello (2009) and Ferriera (2011).…”
Section: Figure2 Capital-weighted Ror By Country Typecontrasting
confidence: 92%
See 1 more Smart Citation
“…Our estimation of macroeconomic ROR is comparable to these in the literature. The majority of the crosscountry studies report highest average ROR to be found in less developed economies (Bigsten, 2000;Banerjee and Duflo, 2005;Izyumov and Alterman, 2005;Bai et al, 2006;Lu and Gao, 2009;Udry and Anagol, 2006;Chou et al, 2016). However our results differ from those reported in Caselli and Feyrer (2007) and some of the follow-up papers including Mello (2009) and Ferriera (2011).…”
Section: Figure2 Capital-weighted Ror By Country Typecontrasting
confidence: 92%
“…Economic theory posits that competition of capital owners should lead to equalization of ROR via intra-and inter-industry capital mobility. Applied to the global economy, this would predict that faster accumulation of capital in developing countries combined with major increases in FDI should contribute to ROR convergence across countries (Chou, et al, 2016). This should reduce GDP losses from capital misallocation.…”
Section: Implications For Economic Growthmentioning
confidence: 99%
“…Then AB rrr = =  and equations 1and 2 Rodrik (2011, p. 192), "[d]ifferences in productivity account for between 80 to 90 percent of the variation in wages around the world.". Finally, for estimations of the levels and trends in the capital profitability across the world (1995)(1996)(1997)(1998)(1999)(2000)(2001)(2002)(2003)(2004)(2005)(2006)(2007), see Chou et al (2016). be correlated with the implementation of economic policies seeking to promote exports through income redistribution from wage incomes, with low propensities to save, to profit incomes, with high propensities to save (Kiefer and Rada, 2015).…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Capital variable is estimated, using the perpetual-inventory method based on the annual investment data (Chou, Izyumov, & Vahaly, 2016;Fraumeni, 1997;Katz & Herman, 1997), as…”
Section: Methodological and Data Issuesmentioning
confidence: 99%
“…The authors will address this issue by dividing the profit rates and wage rates into two parts, from which one is used as the measure of economic efficiency. The uniform profit rate can be divided between the share of profits (Π) within the NI (Π/NI) and the relationship between NI and K (Weisskopf, 1979;Moseley, 1988;Duménil & Lévy, 2002;Wolff, 2003;Caselli & Feyrer, 2007;Ferreira, 2011;Chou, Izyumov, & Vahaly, 2016). Using the same logic, the wage rate (W/L) can be divided between the share of wages (W) in NI (W/NI) and the relationship between NI and L. Relations between NI and K and the NI and L are indicators of capital efficiency and labour force productivity.…”
Section: Empirical Modelmentioning
confidence: 99%